NASAL SKIN CANCER. POSSIBILITIES OF PLASTIC REPLACEMENT OF THE DEFECT DURING SURGICAL TREATMENT - M. A. Kropotov; L. P. Yakovleva; D. K. Stelmakh; I. N. Pustynsky (Опухоли головы и шеи)
The article is determined to the analysis of different types of plastic reconstruction of the external nose with local and combine flaps after radical surgery in oncology. Reconstruction of the external nose is discussed under consideration of experience of our research center, which includes surgical treatment of 35 oncologic patients.